2020
DOI: 10.1038/s41420-020-00338-3
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB1 receptor agonist ACEA alleviates brain ischemia/reperfusion injury via CB1–Drp1 pathway

Abstract: Activation of the cannabinoid CB1 receptor induces neuroprotection against brain ischemia/reperfusion injury (IRI); however, the mechanism is still unknown. In this study, we used oxygen-glucose deprivation/reoxygenation (OGD/R)-induced injury in neuronal cells and middle cerebral artery occlusion (MCAO)-induced brain IRI in rats to mimic ischemic brain injury, and hypothesized that the CB1 receptor agonist arachidonyl-2-chloroethylamide (ACEA) would protect ischemic neurons by inhibiting mitochondrial fission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…In addition, we found that ACEA treatment did not impact the expression of CB2 in both SW480 and SW620 cells, excluding the possibility that the changes observed with ACEA might be caused by CB2. In line with our study, similar observations have been reported by other teams [ 28 31 ], and related mechanisms included enhancing promoter activity via Akt and NF-kB or inducing Human antigen R nucleoplasmic transport. Our results also showed that CB1 activation inhibited the proliferation, migration and invasion of colorectal cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we found that ACEA treatment did not impact the expression of CB2 in both SW480 and SW620 cells, excluding the possibility that the changes observed with ACEA might be caused by CB2. In line with our study, similar observations have been reported by other teams [ 28 31 ], and related mechanisms included enhancing promoter activity via Akt and NF-kB or inducing Human antigen R nucleoplasmic transport. Our results also showed that CB1 activation inhibited the proliferation, migration and invasion of colorectal cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, ACEA is a well described synthetic CB 1 agonist and analogue of AEA [ 164 ]. ACEA has the proclivity to protect ischemic neurons from oxygen-glucose deprivation/reoxygenation and middle cerebral artery occlusion [ 165 ].…”
Section: Synthetic Cannabinoidsmentioning
confidence: 99%
“…First, it is difficult to mimic the pathological process of SAH in vitro, so we only verified our hypothetical mechanism in vivo. Second, a previous study showed that ACEA alleviated cerebral ischemia/reperfusion injury through the CB1R-Drp1 pathway [ 48 ], so we cannot exclude other signaling pathways that improve the prognosis of SAH. These deficiencies would be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%